Grammatical Error Analysis in the English Writing of Indonesian EFL Learners - M Hanif; Eka Susylowati; Wiwik Yulianti (Edu Cendikia: Jurnal Ilmiah Kependidikan, 2026)
Writing in English is an essential skill in today’s globalized world. As one of the most widely used international languages, English plays a crucial role in education, business, technology, and communication. The ability to write effectively in English allows individuals to express ideas clearly, share information, and interact with people from different cultural and linguistic backgrounds. The mastery of English grammar remains a significant challenge for EFL (English as a Foreign Language) learners, particularly in environments where English is not used in everyday communication. This study examines grammatical errors found in written English compositions produced by Indonesian high school students. Using the Error Analysis framework developed by Corder (1967) and expanded by Dulay, Burt, and Krashen (1982), this study aims to identify, categorize, and analyze the most common grammatical errors and their possible sources. The data were obtained from thirty narrative essays written by students in their second year of senior high school in Surabaya. The analysis revealed that errors in verb tense, article usage, subject-verb agreement, preposition use, and word order were most frequently encountered. These findings suggest that both interlingual and intralingual factors contribute significantly to the errors produced by EFL learners. The study concludes with pedagogical implications for improving grammar instruction in EFL contexts, especially in Indonesian classrooms.